Progestin‐based contraception regimens modulate expression of putative HIV risk factors in the vaginal epithelium of pig‐tailed Macaques. (3rd August 2018) - Bosinger, Steven E.; Tharp, Gregory K.; Patel, Nirav B.; Zhao, Chunxia; Payne, Tamika L.; Dietz Ostergaard, Sharon; Butler, Katherine; Ellis, Shanon; Johnson, Ryan L.; Kersh, Ellen N.; McNicholl, Janet M.; Vishwanathan, Sundaram A.
Abstract : Problem: In women, the use of progestin‐based contraception may increase the risk of vaginal HIV acquisition. We previously showed in macaques that there is a significantly higher simian‐human immunodeficiency virus (SHIV) acquisition rate in the luteal phase of the menstrual cycle, which presents a naturally high‐progesterone state, and this may be attributable to altered expression of innate immune factors. We hypothesized that progestin‐based contraception, especially depot medroxyprogesterone acetate (DMPA), would, in a similar way, affect mucosal immune factors that influence HIV acquisition risk. Method of study: We used a pig‐tailed macaque model to evaluate the effects of two progestin‐based contraceptives, DMPA, and levonorgestrel (LNG)/ethinyl estradiol (EE)‐based combined oral contraceptives (COCs), on innate mucosal factors. We compared the vaginal epithelial thickness data from previous studies and used cytokine profiling and microarray analysis to evaluate contraception‐induced molecular changes in the vagina. Results: The administration of DMPA caused a reduction in the thickness of the vaginal epithelium relative to that of the follicular or luteal phase. DMPA also induced a significant increase in vaginal levels of the anti‐inflammatory cytokine IL‐10. Both DMPA‐ and LNG‐based contraception induced a signature of gene expression similar to that of the luteal phase, only more exacerbated, including widespread downregulation of antiviral genes. Conclusion: The use of progestin‐based contraception might engender a milieu that poses an increased risk of HIV acquisition as compared to both the luteal and follicular phases of the menstrual cycle. Abstract : Use of progestin‐based contraception like depot medroxyprogesterone acetate (DMPA) might engender a milieu that poses an increased risk of HIV acquisition as compared to both the luteal and follicular phases of the regular menstrual cycle, by decreasing expression of antiviral factors (example: serpins, ISGs) and increasing expression of HIV‐1 facilitating factors (example: integrins).